Visualizing Individual RuBisCO and Its Assembly into Carboxysomes in Marine Cyanobacteria by Cryo-Electron Tomography. Issue 21 (19th October 2018) - Dai, Wei; Chen, Muyuan; Myers, Christopher; Ludtke, Steven J.; Pettitt, B. Montgomery; King, Jonathan A.; Schmid, Michael F.; Chiu, Wah
Abstract: Cyanobacteria are photosynthetic organisms responsible for ~ 25% of the organic carbon fixation on earth. A key step in carbon fixation is catalyzed by ribulose bisphosphate carboxylase/oxygenase (RuBisCO), the most abundant enzyme in the biosphere. Applying Zernike phase-contrast electron cryo-tomography and automated annotation, we identified individual RuBisCO molecules and their assembly intermediates leading to the formation of carboxysomes inside Syn5 cyanophage infected cyanobacteria Synechococcus sp. WH8109 cells. Surprisingly, more RuBisCO molecules were found to be present as cytosolic free-standing complexes or clusters than as packaged assemblies inside carboxysomes. Cytosolic RuBisCO clusters and partially assembled carboxysomes identified in the cell tomograms support a concurrent assembly model involving both the protein shell and the enclosed RuBisCO. In mature carboxysomes, RuBisCO is neither randomly nor strictly icosahedrally packed within protein shells of variable sizes. A time-averaged molecular dynamics simulation showed a semi-liquid probability distribution of the RuBisCO in carboxysomes and correlated well with carboxysome subtomogram averages. Our structural observations reveal the various stages of RuBisCO assemblies, which could be important for understanding cellular function. Graphical Abstract: Highlights: RuBisCO catalyzes a key step in carbon fixation in cyanobacteria. CryoET identified RuBisCO as free-standing molecules and as packed in carboxysomes. Carboxysome assembles by concurrent recruitment of RuBisCO clusters and the shell. Spatial dispositions of RuBisCO may be related to its physiological conditions.